Fracture resistance of 3-unit zirconia fixed dental prostheses differing in wall thickness fabricated by either 3D-printing or milling - Rues, Stefan; Crocoll, Jannis; Hetzler, Sebastian; Rossipal, Johannes; Rammelsberg, Peter; Zenthöfer, Andreas (Journal of Functional Biomaterials, 2025)
Background: To evaluate the fracture resistance of 3D-printed 3-unit fixed dental prostheses (FDPs) made from tetragonal zirconia polycrystal (3Y-TZP)...
Gesehen am 16.01.2026